2021
DOI: 10.1021/acs.jpclett.1c01548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Mechanism for the Binding between the SARS-CoV-2 Spike Protein and Host Angiotensin-Converting Enzyme II

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is mainly mediated through the interaction between the spike protein (S-pro) of the virus and the host angiotensin-converting enzyme II (ACE2). The attachment of heparan sulfate (HS) to S-pro is necessary for its binding to ACE2. In this study, the binding process of the receptor-binding domain (RBD) of S-pro to ACE2 was explored by enhanced sampling simulations. The free-energy landscape was characterized to elucidate the binding mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…20 The plier feature of RBD is consistent with the binding process and binding characteristics that in the first step of the encounter complex of ACE2 and SARS-CoV-2 RBD, only CR3 (including Y495-Y505) contacts with ACE2, while in the second step, both CR1 (including E471-Y489) and CR3 contact with ACE2. 12 The two ends of the plier determine the key position of binding with ACE2, and then the other residues located on the RBD further bind with ACE2 to transfer the encounter state to the interacting state, enhancing the stability of the binding interface (the position of the plier is shown in Figure 5E). Y489/Y495/L455/Q493 connect with the middle hydrophobic region of the α1-helix on ACE2 PD (Figure 5D), and these connections are the most important part of CR2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The plier feature of RBD is consistent with the binding process and binding characteristics that in the first step of the encounter complex of ACE2 and SARS-CoV-2 RBD, only CR3 (including Y495-Y505) contacts with ACE2, while in the second step, both CR1 (including E471-Y489) and CR3 contact with ACE2. 12 The two ends of the plier determine the key position of binding with ACE2, and then the other residues located on the RBD further bind with ACE2 to transfer the encounter state to the interacting state, enhancing the stability of the binding interface (the position of the plier is shown in Figure 5E). Y489/Y495/L455/Q493 connect with the middle hydrophobic region of the α1-helix on ACE2 PD (Figure 5D), and these connections are the most important part of CR2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Then, theoretical insights of binding details between SARS-CoV-2 RBD and ACE2 can be provided based on the obtained trajectory. Using the all-atom model, main binding details, , binding free energy, and peptide inhibitors have been continuously revealed and found. However, most of the relevant dynamics and interactions within cells (typically, protein–protein docking, rearrangement upon ligand binding or after biochemical reactions, folding) occur on the time scale of microseconds or milliseconds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous inflammatory mediator factors, such as IL-1β, TNF-α, IL-6, TGF-β, and CXCL9, are produced and ultimately contribute to the cytokine storm and ALI [ 86 , 87 ]. Chen et al [ 88 ] found that the spike protein of SARS-CoV-2 mediated viral entry through the binding to ACE2 on the cell surface. Menezes et al [ 89 ] and Li et al [ 90 ] hypothesized that immune cells, including monocytes, neutrophils, lymphocytes, and natural killer cells, could travel to infected areas after breaking endothelial and epithelial barriers.…”
Section: The Role Of Ace2 In Innate Immune-related Cells During Sars-cov-2 Infectionmentioning
confidence: 99%
“…At present, the precise molecular mechanism governing RBD positioning is still being delineated. , To this end, both experimental and theoretical communities have made great effort to build models of SARS-CoV-2 spike protein as well as its complex form with ACE2. , It is well known that current experimental techniques are normally incapable of accessing the full range of large protein conformational changes and only limited to a few local energy-minimum structures. Moreover, it is very difficult to experimentally determine the ionization states of the ionizable residues directly, especially for those buried in the hydrophobic interior of proteins, which can function as pH sensors and trigger the protein structural reorganization of varying amplitudes. Theoretical molecular dynamics (MD) simulations have the capability to capture a broader ensemble of snapshots connecting the various conformational states that a protein can visit and have greatly contributed to our better understanding of the dynamics of the spike protein .…”
Section: Introductionmentioning
confidence: 99%